Perbandingan keefektifan model project-based learning dan problem-based learning ditinjau dari ketercapaian tujuan pembelajaran - Ariyanti, Melda (Jurnal Pendidikan Matematika dan Sains, 2017)
Penelitian ini bertujuan untuk mendeskripsikan keefektifan model Project-Based Learning dan Problem-Based Learning, serta komparasi keefektifan antara model Project-Based Learning dan Problem-Based Learning ditinjau dari prestasi belajar, kemampuan pemecahan masalah, dan minat belajar matematika siswa SMA Kelas XI. Penelitian ini merupakan penelitian eksperimen semu dengan desain pretest-posttest nonequivalent group design. Populasi dalam penelitian ini adalah seluruh siswa kelas XI IPA SMANegeri 2 Kuningan. Sampel penelitian sebanyak dua kelas yang dipilih secara acak. Data hasil penelitian dianalisis dengan MANOVA, dan untuk mengetahui keefektifan model Project-Based Learningdan model Problem-Based Learningmenggunakan uji one sample t-test. Hasil penelitian menunjukkan bahwa model Project-Based Learning dan Problem-Based Learningefektif ditinjau dari minat belajar matematika tetapi tidak efektif ditinjau dari prestasi belajar dan kemampuan pemecahan masalah matematika siswa kelas XI SMA. Tidak terdapat perbedaan keefektifan antara model Project-Based Learning dan Problem-Based Learningditinjau dari prestasi belajar, kemampuan pemecahan masalah, dan minat belajar matematika siswa kelas XI SMA. Kata kunci: Project-Based Learning, Problem-Based Learning, prestasi belajar, kemampuan pemecahan masalah, minat belajar matematika The Effectiveness Comparison of Project-Based Learning and Problem-Based Learning Models in Terms of Achievement of Student’s Learning Objectives Abstract This study aimed to describe the effectiveness of project-based learning and - problem-based learning models and to compare the effectiveness of project-based learning and problem-based learning models viewed from the learning achievement, problem solving ability, and interest in learning mathematics of grade XI students of senior high school. This study was a quasi-experiment study employing the pretest-posttest nonequivalent group design. The population comprised all grade XI science students of SMA Negeri 2 Kuningan. The sample consisted of two classes that were randomly established. The data were analysed by means of MANOVA, and to test the effectiveness of the project-based learning and problem-based learning models, the one sample t-test was used. The results of the study showed that the project-based learning and problem-based learning models were effective viewed from the interest in learning mathematics, but not effective viewed from the learning achievement and problem solving ability of grade XI students of senior high school. There was no difference of effectiveness of project-based learning model and problem-based learning model viewed from the learning achievement, problem solving ability, and interest in learning mathematics of grade XI students of senior high school. Keywords: project-based learning, problem-based learning, learning achievement, problem solving ability, interest in learning mathematics.